Introduction to Qur'anic Wisdwom - Ali, Kausar (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
The human Span of Knowability is limited to boundaries defined by Logical Positivism. The Quran as a book of Knowledge is Message contents revealed from God Almighty. The messages in general may broadly be classified into two broad categories i.e. LEARNING and ACADEMIC. The text contents LEARNING in nature are set of Communication materials calling one to change of its behavior voluntarily i.e. Commanding Response appropriate to Specific Message Contents. The other broader class i.e. ACADEMIC are Text Contents that do not command change of behavior or response expressed through conscience, intents, motivations and actions reflected as ATTITUDES. The holy Quran is explored as Message Contents primarily directed to Change of Behaviour and hence LEARNING in nature. The Quranic Learning Texts are attached with dire consequences in terms of Perpetual bliss and Everlasting sufferings and hence referred as Quranic Wisdoms. The success is the result of commitment and actions in due response to such inherent Wisdoms. It provides with basic ingredients for building of Personalities. The Quranic Wisdoms are communicated through combination of Text forms i.e. MUHKAMAAT and MUTASHABIHAAT. The text contents of MUTASHABIHAAT are essentially Unknowable yet Inferable (through reason) whereas as the texts of MUHKAMAAT are direct, precise, perceptible and observable i.e. Knowable in essence. The progress of behavioral change may be evaluated amid various changing environments and circumstances presented as Quranic Templates. The effective monitoring of change observed across various Quranic Templates can be used as tools for right development of Ordinary Self leading to True Islamic Personalities.